DEMONSTRASI AKTIVITAS FISIK JALAN KAKI UNTUK MENINGKATKAN KEMAMPUAN MERAWAT ANGGOTA KELUARGA YANG MENGALAMI DIABETES MELITUS - Juantika, Noni; Badriah, Siti; Riyana, Asep; Hidayat, Unang Arifin (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2024)
Diabetes Mellitus is a chronic disease caused by the body's inability to produce the hormone insulin Currently Indonesia is in fifth position with the number of diabetics as many as 19.47 million out of 179.72 million population. The purpose of writing this scientific paper is to provide an overview of family nursing care by providing education through demonstrations of walking physical activity to improve family ability to care for family members who have Diabetes Mellitus. Diabetes Mellitus is a high blood glucose level caused by the inability of the pancreas to secrete insulin. Signs and symptoms of Diabetes Mellitus include polyuria, polyphagia and polydipsia. The research method of this scientific paper is to use a qualitative case study design method, namely analyzing the application of walking physical activity by the family to reduce blood sugar levels for 5 days with a frequency of 1 time a day for 30 minutes, data collection is carried out before and after education through demonstration of walking physical activity. The results showed an increase in family independence in caring for family members with Diabetes Mellitus, which is at level III independence with 6 criteria. The conclusion is that education through demonstration of walking physical activity is effective for improving the ability of families to care for family members with Diabetes Mellitus, but depends on family understanding which can affect the success of therapy. for further researchers, it is hoped that it can improve educationalmethods about the application of walking physical activity to families so that families are maximized in doing walking physical activity, so that maximum results are obtained.